An Assessment of Operational Challenges in Udayapur Cement Industry - Neupane, Gopi Krishna; Pant, Sushil Kumar (Journal of Advanced Academic Research, 2026)
The research discusses the poor performance of Udayapur Cement Industries Ltd. (UCIL), the largest state owned cement factory in Nepal and discusses ways through which it can be restored to its previous glory. Having been a dominating unit initially in the domestic market, UCIL is now functioning at a meager 30 to 35 out of the 100 percent installed capacity, compared to the worldwide standards of 80 to 90 and even the rivals of the company, which operate at 70 to 80 percent. The study is devoted to the areas of production, logistics, and workforce management in order to determine which problems are hurting performance. The qualitative case study approach was adopted with two sources of evidence firsthand managerial reflections of thirty months experience working at UCIL and secondary data of the industry reports, government statistics and comparison with competitors. These have been examined at a thematic level in order to identify structural inefficiencies as well as contextual constraints. The results point to various difficulties. Old machines, high breakdown rates and inappropriate matching spare parts have greatly lowered the efficiency on production. A weak input quality that comprises poor quality of coal contribute to a weakened cement strength. The inefficiencies in workforce are severe, as the interference of unions, lack of discipline and excessive labor costs stand at an average of NPR 100,000 per employee every month; this is five times the averages in the private sector. It, therefore, results in an average of NPR 650 per 50-kg bag as the cost of production, which is usually higher than the selling price causing losses of more than NPR 360 million by FY 2020. The weak marketing and malpractice by dealers have also cut the sales down to 23,000 bags a day. The research suggests the short-term solutions to be taken in the nearest future, such as the rehabilitation of the machine, the control over raw materials gained more strictly, the accountability of the working staff, and the marketing changes. To be long-term sustainable, the company should implement such strategies as public-private partnerships, the creation of 10,000 TPD plant to exploit the limestone reserves in Sindhali, the use of renewable energy, and the modernization of logistics. The combination of these measures will be able to bring back the competitiveness, decrease the reliance on imports of clinker, and make the cement industry of Nepal more robust.